PENDAMPINGAN OLAHAN PANGAN SEHAT DAN PERIZINAN BERUSAHA PRODUSEN KUE TRADISIONAL RW 11 SANGGAR INDAH BANJARAN KECAMATAN CANGKUANG KABUPATEN BANDUNG - Triyani, Yani; Puspita, Sara; Surialaga, Samsudin; Hendryanny, Eka (Universitas Mataram, 2024)
The impact of the Covid-19 pandemic on traditional cake businesses in the study area affects the family economy. It was more difficult while the burden of basic needs that must be met was increasing. This community of traditional cake producers has the potential to be developed and can improve the welfare of people’s lives. However, most need to learn how to process healthy food and do not have business permits. The service aims to provide knowledge and assistance so that traditional cake producers are aware of safe and healthy, as well as encouraging the ownership of business permits and halal certificationso that they can improve the quality of their products and businesses. The service method is carried out in several stages, the activity stage consists of 2 stages, first stage is delivering knowledge on healthy and halal food processing by Islam Bandung (Unisba) experts and Indonesian Food and Drug Authority in collaboration with the Unisba medical faculty, which is carried out in a hybrid meeting. The second stage is assistance in the form of interactive dialogue and hands-on workshops to get to know the flow of procedures for making and managing Home Industrial Food and Business Identification Number as well as halal certification of a product. The results is traditional cake producers seemed enthusiastic when they received knowledge and assistance regarding the importance of the quality of processed products and business permits for developing their business. Further assistance activities are needed, in terms of PIRT management and NIB ownership, as well as halal certification of processed products so that efforts to improve the quality and business development of traditional cake producers can be further realized.